EFEKTIFITAS METODE SMALL GROUP DISCUSSION UNTUK MENINGKATKAN KEMAMPUAN MENULIS BAHASA INGGRIS PADA SISWA KELAS 5 DI SDN 1 CISAAT GADIS - Anisa Alawiyyah; Siti Apsoh; Putri Amalia Irantina Kurnella (Nusantara Hasana Berdikari, 2022)
The objectives of this research are to find out whether there is improvement in students’ writing ability and what aspect improves the most after being taught through small group discussion method. This research is basically quantitative research which uses one group pretest-posttest design. The population of this research was the fifth grade students of SDN 1 Cisaat Gadis in the academic year 2021/2022. The result of the research shown that there is improvement in the students’ writing ability after being taught by using small group discussion method. It can be seen from the increase of the result of the pretest and posttest. The data are analyzed by using t-test value in which the significance was determined by p<0.05. The aspect improves the most is content, since small group discussion method writing provides the students multiple input by sharing and developing the ideas collaboratively. It can be said that there is improvement of students’ writing skill in writing text. Besides, the second finding shown that there is a significant connection in the using of small group discussion method toward improving student’s writing ability. Briefly, referring to the result above, it can be said that small group discussion method can be applied to improve students’ ability in writing text.